Sinai and the saints : reading old covenant laws for the new covenant community - Todd, James M., 1981- (Downers Grove : InterVarsity Press, 2017)
What should Christians do with all the laws in the Old Testament? The Old Testament tells the story of the beginnings of God's salvation history, and it is part of the authoritative canon of Scripture affirmed by the church. But what role should the laws of the old covenant play in the lives of those living under the new covenant? Can Christians embrace the commandment to "love the Lord your God with all your heart and with all your soul and with all your strength" but ignore the laws regarding clean and unclean food? Some have suggested that Christians remain under the moral laws of the old covenant, while others have argued that some of the Old Testament laws -- for example, the Ten Commandments--still apply to Christians. James Todd makes a bold claim by contending that as followers of Jesus Christ who stand under a new covenant, Christians are no longer subject to any of the Old Testament laws. Focusing on the laws of the Pentateuch, he then addresses the proper role and benefits of the Old Testament laws in the Christian life. With wit and insight, Todd helps Christians to understand how the laws given to the people of Israel at Mount Sinai should be read by those called to live as saints. - back of book.
What do I do with all these laws? -- Which laws are we discussing? -- What are my options? approaches to the old covenant laws -- In the beginning, not thou shalt not -- The rest of the story (part 1): Israel at Sinai -- The rest of the story (part 2): before and after Sinai -- Thou shalt not remove them: what about the Ten Commandments? -- Does this mean I can do whatever I want? -- Why should we read the laws? -- Can I have the good news? the hope of the Pentateuch -- Back to the beginning: the law in the early church and the contemporary church -- How should Christians use the Hebrew Bible to address homosexuality? -- The second commandment and images in worship -- Challenges to my position.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Relation to the New Testament; Bible; Jewish law; Christianity and law; Christianity and law; Jewish law; RELIGION / Biblical Studies / Old Testament; Criticism, interpretation, etc; Electronic books